A randomized, phase IIa exploratory trial to assess the safety and preliminary efficacy of LEO 43204 in patients with actinic keratosis. (9th January 2016) - Sinnya, S.; Tan, J.M.; Prow, T.W.; Primiero, C.; McEniery, E.; Selmer, J.; Østerdal, M.L.; Soyer, H.P.
Abstract : What's already known about this topic? Field cancerization, comprising actinic keratoses (AKs) and subclinical, preneoplastic epithelial changes, is an increasing problem in fair‐skinned populations. Improved topical AK treatments with increased efficacy and tolerability are needed. What does this study add? The novel ingenol derivative LEO 43204 (0·075%) reduced AK count more than ingenol mebutate gel. A dose–response relationship for local skin responses was noted across the LEO 43204 concentrations tested. Linked Comment: Werner and Nast, Br J Dermatol 2016; 174: 260–261 . Summary: Background: LEO 43204 is a novel ingenol derivative in development for the treatment of actinic keratosis. Objectives: To compare the safety and preliminary efficacy of three doses of LEO 43204 with ingenol mebutate in actinic keratoses (AKs). Methods: Patients with at least three visible, discrete, nonkeratotic AKs on four separate selected treatment areas on the forearms received LEO 43204 gel (0·025%, 0·05% and 0·075%) and ingenol mebutate 0·05% gel, by investigator‐blinded, randomized allocation, for 2 consecutive days. Patients were assessed at 8 weeks. Primary outcomes included maximum composite local skin response (LSR) score and adverse events (AEs). Secondary outcomes included a reduction in the number of visible AKs. Results: Forty patients completed the trial. For all treatments, mean LSR scores peaked at week 1, and were below baseline by week 8. Mean maximum composite LSR scores for LEO 43204 0·025%, 0·05% and 0·075% were 9·2 (Dunnett adjusted P = 0·02), 10·1 (Dunnett adjusted P = 0·90) and 11·2 (Dunnett adjusted P < 0·01), respectively, vs. ingenol mebutate 0·05% gel (10·0). The most frequent AEs across all treatments were application site pruritus, burning sensation and tenderness. Mean reduction in the number of AKs was comparable for ingenol mebutate and the two lowest doses of LEO 43204 (71·9–73·1%), but LEO 43204 0·075% gave a significantly larger reduction (81·8%; Dunnett adjusted P = 0·04). Conclusions: LEO 43204 had a similar safety profile to ingenol mebutate and a dose–response relationship for LSRs was demonstrated. The highest LEO 43204 dose (0·075%) significantly reduced the AK count when compared with ingenol mebutate.